Organizing a Medical Conference: Management Perspective - Gajuryal, Sharad Hari; Shrestha, Resha; Satyal, Narayan; Pant, Basant (Nepalese Medical Journal, 2020)
It is an incredibly formidable as well as meritorious task to plan and implement a successful medical conference. Organizing a medical conference requires a tremendous amount of planning, preparation, lots of pre conference works, and working on logistics to achieve its vision and goal. The two most important aspects for the success of any event is planning and implementation which requires a plenty of brainstorming sessions and meetings, and for medical practitioners and academicians, we are confronted with the dual role of organizing the conference as well as regular work juggling. Despite the fact that medical conferences play a major role in ongoing professional development, academic growth, and networking, there is little guidance in form of literature for those who want to hold a conference inbound or outbound. This paper seeks to incorporate all the possible steps, plans and procedures in order to organize a successful conference.